Peran Probiotik terhadap Tingkat Rekurensi Bakterial Vaginosis - Cynthia Sandra Kuncoro (Syntax Corporation Indonesia, 2022)
Known as the most common cause of vaginal discharge in women of reproductive age, Bacterial Vaginosis (BV) is characterized by shfting of lactobacillus-dominated vagina microbiota to facultative or obligate anaerob bacteria. Inspite of first line treatment showing high efficacy toward BV, BV recurrences still frequently occur . This review would describe the result of current clinical trials regarding probiotic as alternative therapy to reduce the recurrence of BV. Literature search was conducted by using PubMed and Cochrane database with keyword probiotics, lactobacillus, recurrent, and bacterial vaginosis. It results on 9 clinical trials, which match to inclusion criteria and will be evaluated further. Diverse probiotic strains, dosage and duration of probiotics lead to varied outcomes in this review. In several studies, probiotic has potency in reducing the recurrence of BV compared to placebo. However, further large scale studies are still needed to determine the precised duration and dosage of probiotics given.